EFFECT OF HEAT TREATMENT ON THE WEAR AND CORROSION BEHAVIORS OF A GRAY CAST IRON COATED WITH A COLMONOY 88 ALLOY DEPOSITED BY HIGH VELOCITY OXYGEN FUEL (HVOF) THERMAL SPRAY - (:unkn) unknown (CROATIAN METALLURGICAL SOC, 2013)
The present work has been conducted in order to determine the influence of heat treatment on the wear and corrosion behaviours of a gray cast iron substrate coated with a Ni base coating deposited by HVOF thermal spray. The wear resistance of the coatings was obtained using a reciprocating wear tester by rubbing a 10 mm diameter steel ball on the coatings at normal atmospheric conditions. Corrosion tests were performed using potentiodynamic polarization measurements in a 3,5 % NaCl solution. It was observed that the corrosion and wear resistance of the coatings increased along with the reduction of porosity and roughness by the heat treatment.
Keywords: Corrosion; HVOF; Ni-based coating; post-heat treatment; wear; COATINGS; CO